2022
DOI: 10.7759/cureus.23050
|View full text |Cite
|
Sign up to set email alerts
|

Appendiceal Diverticulitis Presenting as Acute Appendicitis and Diagnosed After Appendectomy

Abstract: IntroductionDiverticular disease of the appendix (DDA) is a rare appendiceal pathology. It is usually present similar to acute appendicitis. Because of its rarity, the DDA is poorly comprehended. This study evaluates the incidence, clinical and pathological characteristics of appendiceal diverticulitis diagnosed after appendectomy. MethodsWe performed a retrospective analysis of patients who underwent appendectomy between January 2016 and January 2022 at the Istanbul Sultanbeyli State Hospital General Surgery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…There are two different types of appendiceal diverticula: congenital (incidence - 0.014%) and acquired (incidence - 1.9%). Acquired-type diverticula occur secondary to increased pressure within the appendiceal lumen, leading to an outpouching of the mucosa through the muscularis propria at low-pressure points along the mesenteric and antimesenteric borders [ 3 ]. Causes for this may include the presence of a fecalith, proximal tumours, and excess mucus [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two different types of appendiceal diverticula: congenital (incidence - 0.014%) and acquired (incidence - 1.9%). Acquired-type diverticula occur secondary to increased pressure within the appendiceal lumen, leading to an outpouching of the mucosa through the muscularis propria at low-pressure points along the mesenteric and antimesenteric borders [ 3 ]. Causes for this may include the presence of a fecalith, proximal tumours, and excess mucus [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms of diverticulitis of the appendix are similar to those of acute appendicitis, which is the most common pathology of the appendix. Diverticulitis of the appendix is four times more likely to lead to perforation when compared to appendicitis and may be a sign of an underlying neoplasm [ 3 ]. Therefore, it is extremely important to distinguish diverticulitis of the appendix from appendicitis.…”
Section: Introductionmentioning
confidence: 99%
“…This evolution has seen the shift from diagnosis based purely on clinical features [ 5 , 6 ], to the inclusion of laboratory investigations [ 7 - 9 ], and lately confirmatory medical imaging techniques [ 10 , 11 ]. Furthermore, histological assessment of the excised appendix has now become imperative as there are other disease conditions that may mimic acute appendicitis such as mucocele and carcinoid tumor of the appendix, chronic granulomatous infections, actinomycosis, endometriosis, lymphoma, and helminthiasis [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Acute appendicitis has been reported as the most common reason for appendicectomy in Northern Saudi Arabia [ 20 ]. Evidence shows that intra-operative normal appendices may have an unusual incidental result at pathological evaluation, and the practice of routine pathological examination of appendectomy specimens varies between centers [ 12 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Early diagnosis and management are crucial to improve morbidity and mortality [1]. The differential diagnosis of acute appendicitis includes a wide variety of medical and surgical conditions, which are well described in the Ergenç et al study [2]. Ergenç et al reported that diverticular disease of the appendix (DDA) has a similar presentation to acute appendicitis, and it is considered a rare pathology of the appendix [2].…”
Section: Introductionmentioning
confidence: 99%